Exam ref 70-347 enabling Office 365 services - Thomas, Orin 1973- (Microsoft Press, 2015)
Prepare for Microsoft Exam 70-347--and help demonstrate your real-world mastery of the skills needed to help securely and efficiently provide Microsoft Office 365 services in any environment. Designed for experienced IT pros ready to advance their status, Exam Ref focuses on the critical-thinking and decision-making acumen needed for success at the MCSA level. Focus on the expertise measured by these objectives: Manage clients and end-user devices Provision Microsoft SharePoint Online site collections Configure Microsoft Exchange Online and Skype for Business for end users Plan for Exchange Online and Skype for Business This Microsoft Exam Ref : Organizes its coverage by exam objectives Features strategic, what-if scenarios to challenge you Provides exam preparation tips written by a top trainer, consultant, and sysadmin Assumes you have experience with the Office 365 Admin Center and an understanding of Exchange Online, Skype for Business, SharePoint Online, Office 365 ProPlus, and Microsoft Azure Active Directory.